ANALYSIS OF FACTORS INFLUENCING DRUG ABUSE CASES USING MODELS GEOGRAPHICALLY WEIGHTED REGRESSION (GWR) IN INDONESIA - Nurfebriyanti, Endah; Nasution, Hamidah; Cipta, Hendra (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
The number of drug abuse cases in Indonesia from 2015-2020 tends to fluctuate. Factors influencing drug abuse cases in each region are thought to vary according to geographical location. This geographic effect is known as spatial heterogeneity. Spatial heterogeneity was analyzed usingGeographically Weighted Regression(GWR). This study aims to model the factors that influence drug abuse in every province in Indonesia, namely Economic Situation (X1), Association/Environment (X2), Convenience (X3) and Lack of Supervision (X4) using a Gaussian kernel. The results showed that the GWR with the Gaussian kernel is better at estimating the model because it has a higher value, namely R^2 with 90.94% and the AIC value equals 598.798979. Factors that significantly affect the number of cases of drug abuse in Indonesia are Economic Conditions, Association/Environment, Convenience and Lack of Supervision.